Comorbidity, lifestyle factors, and sexual satisfaction among Chinese cancer survivors. (13th July 2021) - Wang, Jingya; Zhao, Jie; Zhang, Chenggang; Zhang, Yuxin; Jiang, Nan; Wei, Xiaomin; Wang, Jiwei; Yu, Jinming
Abstract: Objectives: This study aims to explore the prevalence of sexual satisfaction among Chinese cancer survivors, and explore the association of sexual satisfaction with comorbidity and lifestyle factors. Methods: A cross‐sectional study was performed among 3996 Chinese cancer survivors recruited at Shanghai Cancer Rehabilitation Club from March to April 2017. Data were collected through self‐reported questionnaires. The questionnaire includes information about demographic, cancer characteristics, comorbidities, lifestyle factors, and sexual satisfaction. Sexual satisfaction was measured by a single‐item scale. The distribution of sexual satisfaction among different demographic and cancer characteristics was compared using the chi‐squared test. Logistic regression models were conducted to assess the effects of lifestyle factors, comorbidities on sexual satisfaction after adjustment for demographic and cancer characteristics. Results: More than 40% of male and female cancer survivors reported no sexual satisfaction. Sexual satisfaction of cancer survivors is significantly associated with both the number and the type of comorbidities. Heart disease, musculoskeletal system disease, diabetes, and hyperlipidemia are the comorbidities significantly associated with sexual satisfaction of cancer survivors. Lifestyle factors other than smoking, including exercise or fitness, drinking alcohol, and eating fruits and vegetables are significantly correlated with sexual satisfaction. Besides, all of the above associations show gender differences. In addition, demographic characteristics include sex, age, marital status, living status, and average monthly income are also significantly associated with sexual satisfaction of cancer survivors. Conclusion: Comorbidity and lifestyle factors are associated with sexual satisfaction of cancer survivors, and the associations show gender differences. Improving the lifestyles of cancer survivors, and controlling and reducing their comorbidities are important for improving their sexual satisfaction. Abstract : This study aims to investigate the prevalence of sexual satisfaction among Chinese cancer survivors, and explore the association of sexual satisfaction with comorbidity and lifestyle factors. Comorbidity and lifestyle factors are associated with sexual satisfaction of cancer survivors, and the associations show gender differences. Improving the lifestyles of cancer survivors, and controlling and reducing their comorbidities are important for improving their sexual satisfaction.